Thinking and Killing Philosophical Discourse in the Shadow of the Third Reich - Segev, Alon (De Gruyter, 2013)
This book explores the phenomenon of the Third Reich from a philosophical perspective. It concentrates on the ways in which the subjects and experiences of Nazi Germany, the Holocaust and Anti-Semitism are conceived by eight German thinkers from the Continental tradition. These eight intellectuals include Martin Heidegger, Hannah Arendt, Karl Löwith, Carl Schmitt, Ernst Jünger, Jean Améry, Hans-Georg Gadamer, and Jan Assmann. Based on careful philosophical examinations of both known and unknown texts of these eight thinkers (including an English translation of two forgotten texts by Schmitt and Jünger), this study exposes and then explores the tension between ideology and philosophy, between submission to authority and genuine critical thinking, all of which constitute the essence of the Continental philosophical tradition.